Clinical applications of basophil activation test: a review - Ya-Dong GAO; Jin-Jin ZHANG; Guang-Hui LIU (Yixue xinzhi zazhi)
Basophils are one of the most important effector cells involved in IgE-mediated type I hypersensitivity and type 2 inflammation. Basophil activation test (BAT) simulates in vivo type I hyper-sensitivity. Flow cytometry is used in BAT to detect the expression level of specific surface markers on basophils after allergen stimulation, hence reflecting the degree of activation and status of basophils. As an allergen test in vitro, BAT shows good safety and high specificity. In clinical practice, it can be used for the auxiliary diagnosis of diseases such as food or drug allergy, airway allergic diseases, hymenoptera venom allergy and anaphylaxis. In addition, it can help to predict and monitor the efficacy of specific immunotherapy for different allergens. Allergen reagents, operational procedures and interpretation methods need to be further standardized to facilitate the popularization and application of BAT.